Housing Insecurity Over Time: Exploratory Analysis of Repeat Housing-Service Use Within A Single Local Government Area in Wales - Thomas, Ian; Mackie, Peter (International Journal of Population Data Science, 2020)
Introduction In their 2019 homelessness strategy, Welsh Government make the commitment for a Wales where homelessness is a rare experience, and if it does occur is brief and non-recurrent. However, measuring repeated homelessness/housing issues (or ‘non-recurrence’) has thus far not been possible in Wales, with only aggregate data collected nationally on interactions between people and local government housing-services. Drawing on recently available individual level data from a single local government area in Wales, we set out to explore repeated use of housing/homelessness services. Objectives and Approach The sample used in this analysis relates to approximately 6,000 individuals who sought assistance from Swansea local government housing-service during a four-year period, from January 2012 to December 2015. In order to group people with similar epeated interactions with the housing service, we use analyses that firstly aggregate the total time spent interacting with the service and over how many distinct periods (Cluster analysis), and secondly explore patterns in sequences of month-by-month service use histories (Sequence Analysis). Results We describe the patterns of repeat housing-service use identified through the Cluster Analysis and the Sequence Analysis, and the characteristics of each group. We also directly compare the ‘time-aggregating’ and ‘time-patterned’ based approaches to classifying people, in order to illustrate the differences that methodology can bring to our conceptualisation of repeat housing service use. Conclusion / Implications The findings from this study have the potential to inform Wales’ move away from aggregate to individual level national homelessness data collection, by illustrating how individual level data can be used to provide new insights into homelessness. Exploring different conceptualisations of repeated housing-service use can also inform future developments in the measurement of repeat housing problems, and therefore monitor progress in achieving a Wales where homelessness is rare, brief, and non-recurrent.